THE IMPACT OF FIRST LANGUAGE TOWARD SECOND LANGUAGE ACQUISITION - Mutiara Utami; Monika, Tiara; Agustin, , Debi; Habibi, Muhammad (Universitas Muhammadiyah Muara Bungo, 2024)
ABSTRACT This research was conducted to find out and to explore the impact of the first language towards second language acquisition. To gain the data, this research involved 5 participants from students at Muhammadiyah University Muara Bungo. They are students of English Education Department, Semester 5. This research was conducted using qualitative methods, the data was collected through interview. Based on the data, there are those who encounter difficulties in learning English language, especially environmental factors and the first language. However, they still learn English by watching films, listening to songs and social media. Keywords : Impact, First Language, Second Language, Acquisition